Rancang Bangun Website Smartbeez sebagai Platform Edukasi Parenting dan Calistung Anak Berbasis Waterfall - Rasyade, Maura Aqlaila; Voutama, Apriade (Jurnal Teknologi Terpadu, 2025)
The development of digital technology has brought convenience to various aspects of life, including education. Websites have become one of the most effective solutions for providing access to learning, especially for parents and children. This study aims to design and develop the SmartBeez website as an educational platform for parenting and basic literacy (reading, writing, and arithmetic) for children, using the Waterfall model. System development consists of several stages, including requirements analysis, system design, implementation, testing, and maintenance. The website targets two main user groups, which are parents and children aged 5 to 12 years. Parents can access parenting materials, while children can learn basic literacy skills through interactive content. Data were collected through observation and literature. The system design is illustrated using Unified Modeling Language (UML) to represent the system flow visually and structurally. Testing was conducted using the black-box testing method to ensure that each feature works according to user needs. The results show that the SmartBeez website can serve as an educational platform that helps parents implement more effective parenting methods, while also providing an engaging and structured learning experience for children.